2006
DOI: 10.1149/1.2146893
|View full text |Cite
|
Sign up to set email alerts
|

Negative Shifts in the Flatband Potential by Adsorption of Iodide Ions on Surface-Alkylated and Pt Nanodotted n-Si(111) Electrodes for Improvement of Solar Cell Characteristics

Abstract: The flatband potential (UFB) and solar cell characteristics for surface-alkylated and Pt nanodotted n-Si(111) electrodes have been studied in normalI3−∕normalI− redox electrolytes using various alkyls as the surface-terminating group. It is found that the UFB for the surface-methylated and Pt nanodotted n-Si(111) electrodes shifts toward the negative with increasing I− concentration in the electrolyte, in parallel to the equilibrium redox potential Ueq(I3−∕I−) , and thus the open-circuit photovoltage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…As seen from the data, different positive and negative potential shifts occurred. Directions and magnitudes of potential shifts obtained for the substances and brands of carbons studied are shown in Tables 3 and 4 6 ] on AR-3A (269 mV and 252 mV, respectively). Thus, it was shown that interaction between inorganic salts and activated carbons did not lead to adsorption of either cations or anions, since the total amounts of iron, chromium, and sulfur was unchanged after the contact of the salt solutions with carbons.…”
Section: Resultsmentioning
confidence: 99%
“…As seen from the data, different positive and negative potential shifts occurred. Directions and magnitudes of potential shifts obtained for the substances and brands of carbons studied are shown in Tables 3 and 4 6 ] on AR-3A (269 mV and 252 mV, respectively). Thus, it was shown that interaction between inorganic salts and activated carbons did not lead to adsorption of either cations or anions, since the total amounts of iron, chromium, and sulfur was unchanged after the contact of the salt solutions with carbons.…”
Section: Resultsmentioning
confidence: 99%
“…Directions and magnitudes of potential shifts obtained for the substances and brands of carbons studied are shown in Tables 3 and 4. As seen in these tables, K 2 Cr 2 O 7 , ZnSO 4 , and K 3 [Fe(CN) 6 ] gave only positive potential shifts, whose magnitudes depended on the oxidation state of the activated carbon; the greatest positive shifts occurred with K 2 Cr 2 O 7 and K 3 [Fe(CN) 6 ] on AR-3A (269 mV and 252 mV, respectively). The interaction between inorganic substances K 4 [Fe(CN) 6 ], K 3 [Fe(CN) 6 ], and K 2 Cr 2 O 7 and activated carbons SKT-6A and AKU was studied in more detail.…”
Section: Ecs Transactions 11 (20) 19-28 (2008)mentioning
confidence: 71%
“…The following inorganic salts and organic compounds were studied: Na 2 SO 4 , Na 2 SO 3 , CuSO 4 , ZnSO 4 , NaNO 3 , NaNO 2 , K 2 Cr 2 O 7 , K 4 [Fe(CN) 6 Table 1. Potentials of activated carbon were measured in time against the silver/silver chloride reference electrode.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations